Numérique et enseignement-apprentissage des langues en Lansad – Quand, comment, pourquoi ? - Françoise Demaizière; Muriel Grosbois (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Language for Specific Purposes (LSP) is key to setting up technology-enhanced language learning environments in higher education because of both high demand and low financial investment in that sector. LSP lends itself quite easily to innovation and associated research since it does not have to comply to pre-established course descriptions for example. Moreover, those who teach in "traditional" fields usually do not object to innovation happening elsewhere. In this opening text, it is thus through LSP that the following questions regarding language learning in a technology-enhanced context will be tackled: when, how and why? Although most remarks are targeted towards higher education, they may apply to other levels too.